2019
DOI: 10.1021/acs.joc.9b01564
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Anmindenol A and Its Application to the Design, Synthesis, and Biological Evaluation of Derivatives Thereof

Abstract: The first total synthesis of anmindenol A is described in four steps. A notable feature of the synthetic route includes the efficient construction of the 3,10-dialkylsubstituted benzofulvene core via a stereoselective vinylogous Stork enamine aldol condensation. The strategy provided a blueprint for the practical preparation of derivatives with modifications in the C-10 alkyl substituents. The novel derivatives inhibited nitric oxide production in stimulated RAW 264.7 macrophage cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In particular, the highly functionalized framework of 9 was envisaged to be generated via the substrate‐controlled regio‐ and stereocontrol caused by the steric nature of the methoxy group at the C‐7 position. The ( E , Z )‐ δ ‐ i Pr‐ α , β , γ , δ ‐unsaturated aldehyde 9 could be stereoselectively synthesized from a critical vinylogous Stork enamine aldol condensation (VSEAC) of the stable enamine precursor 10 . The enamine moiety of 10 would be regioselectively introduced by a solvent‐free methylenation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the highly functionalized framework of 9 was envisaged to be generated via the substrate‐controlled regio‐ and stereocontrol caused by the steric nature of the methoxy group at the C‐7 position. The ( E , Z )‐ δ ‐ i Pr‐ α , β , γ , δ ‐unsaturated aldehyde 9 could be stereoselectively synthesized from a critical vinylogous Stork enamine aldol condensation (VSEAC) of the stable enamine precursor 10 . The enamine moiety of 10 would be regioselectively introduced by a solvent‐free methylenation.…”
Section: Resultsmentioning
confidence: 99%
“…The regioisomeric mixture of 10 was easily separable by chromatography. With the desired precursor 10 in hand, we investigated a stereoselective vinylogous Stork enamine aldol condensation . The key condensation with isobutyraldehyde in the presence of Bu 2 BOTf in THF proceeded smoothly to generate the desired ( E , Z )‐ δ ‐ i Pr‐ α , β , γ , δ ‐unsaturated aldehyde 9 in 81 % yield and with excellent stereoselectivity (> 20:1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This on ketone reduction followed by dehydration resulted in indene, which on treatment with N,N‐dimethylformamide dimethyl acetal (DMP.DMA) provided the desired enamine 361 in good regioselectivity (>3.5:1). The latter on stereoselective vinylogous Stork enamine aldol condensation [ 128 ] gave aldehyde 362 with excellent stereoselectivity ( E/Z >20:1). Having the common intermediate, next the reduction of aldehyde to alcohol 363 , and Negishi cross‐coupling furnished nicotianasesterpene A ( 364 ), while the Stille cross‐coupling [ 129 ] gave nicotianasesterpene B ( 365 ).…”
Section: Miscellaneous Approaches In Pgf Total Synthesis Of Naturamentioning
confidence: 99%
“…Benzofulvene derivatives play important roles in medicinal chemistry and material science . Recent studies identified a number of benzofulvene-containing natural products with remarkable biological and pharmaceutical potential . In addition, functionalized benzofulvenes are also versatile building blocks widely used among the synthetic community …”
mentioning
confidence: 99%